Fourier transform infrared spectroscopy in treated woods deteriorated by a white rot fungus - Ezequiel Gallio; Paula Zanatta; Débora Duarte Ribes; Marília Lazarotto; Darci Alberto Gatto; Rafael Beltrame (Maderas: Ciencia y Tecnología, 2018)
This study aimed to analyze chemical changes by Fourier Transform Infrared Spectroscopy of Eucalyptus dunnii and Pinus elliottii treated woods subjected to an accelerated decay test with the white rot fungus Ganoderma applanatum. The wood test specimens (2.5x2.5x0.9 cm) were impregnated with preservative solutions of chromated copper borate and synthetic pyrethroids and carbamates with 6% concentration by a vaccum-pressure process. After a decay test of 16 weeks, the chemical changes of the treated and untreated wood samples were evaluated by Fourier Transform Infrared Spectroscopy. It was observed that the rot fungus attack caused a variation in the intensity and a displacement of spectrum peaks, indicating a change to the woods’ chemical composition after fungal exposure. The lignin / carbohydrate ratio indicated that the fungus had no preference for a specific cell wall component, pointing to a simultaneous deterioration of cellulose, hemicellulose and lignin in the treated and untreated woods. Finally, the Fourier Transform Infrared Spectroscopy technique, together with the lignin / carbohydrate ratio analysis, proved efficient in the study of the variation of the wood chemical modifications deteriorated by rot fungi.